Effects of Freeze Vacuum Drying Combined with Hot Air Drying on the Sensory Quality, Active Components, Moisture Mobility, Odors, and Microstructure of Kiwifruits. (7th March 2019) - Zhang, Lihui; Qiao, Yu; Wang, Chao; Liao, Li; Liu, Lu; Shi, Defang; An, Kejing; Hu, Jianzhong; Xu, Qing
Abstract : In this study, freeze vacuum drying (FVD), hot air drying (AD), and FVD combined with AD (FVD-AD) were used to dry kiwifruits. Dried products were analyzed comprehensively on their sensory quality, active components, moisture mobility, odors, and microstructure. Results showed that the FVD-AD saved time by 38.22% compared with FVD while maintaining an acceptable product quality. The antioxidant properties of FVD-AD were lower than those of FVD but significantly higher than those of AD. Moreover, compared with FVD products, FVD-AD products were moderately hard (5252.71 ± 33.53 g) and improved in color, bound water, and microstructure. Additionally, FVD-AD consumed lesser drying time and energy than FD. According to cluster analysis, the odors of FVD-AD products were similar to those of the fresh ones. Principal component analysis of physicochemical and drying cost indicated that FVD-AD was a promising processing technique for functional kiwifruit snacks.